PTEROCARPUS ANGOLENSIS CRUDE EXTRACTS INDUCE THE EXPRESSION OF COLLAGEN TYPE II IN ARTICULAR CARTILAGE IN VITRO - Ssemakalu, Cornelius Cano; Razwinani, Mapula; Maepa, Makwese Johannes; Motaung, Keolebogile Shirley (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Pterocarpus angolensis (P. angolensis) is a large deciduous tree native to Sub-Saharan Africa. This tree has traditionally been used to treat malaria, gonorrhoea, inflammation and wounds. The use of P. angolensis for tissue engineering has not been explored. This study investigated the potential of the bark and root water extracts of P. angolensis to induce the expression of collagen type II protein in the articular chondrocytes. Materials and Methods: Surface and middle zone chondrocytes, as well as explants, were stimulated with crude root and bark plant extracts at different concentrations. After 96 hours of stimulation, microscopic observation, XCELLigence assay and collagen type II ELISA, histology and immunohistochemistry assays were done. Results and Conclusion: Results showed no significant difference in the cell index between the controls and chondrocytes that had been treated with the plant extracts at concentrations of 15 and 30 μg/ml. A significant increase in the expression of collagen type II protein by the chondrocytes was observed and found to be optimal at a concentration of 30 μg/ml. There was an increase in the production of proteoglycans. However, the plant extracts at a concentration of 50 μg/ml induced apoptosis in the middle zone chondrocytes. These results show the potential of P. angolensis extracts in chondrocyte tissue regeneration. This potential could be exploited in the treatment of osteoarthritis.